2020
DOI: 10.2147/dmso.s240645
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Adding Insulin Glargine on Glycemic Control in Critically Ill Patients Admitted to Intensive Care Units: A Prospective Randomized Controlled Study</p>

Abstract: Objective: We aimed to examine the effects of adding a longer-acting insulin glargine to existing glucose control on reducing blood-glucose fluctuations in an intensive care unit (ICU). Methods: A total of 110 patients randomly received adjuvant insulin glargine 15 IU/day (glargine) or placebo (control), in addition to daily infusion of insulin to maintain glucose levels at a target of 140-180 mg/dL. End points were mean and variance of blood glucose and frequency of hypoglycemia, hyperglycemia, ICU stay, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…In accordance with our results, Nader et al (21) evaluated 110 patients who, besides daily insulin infusions, were randomly assigned to receive adjuvant placebo (control) or insulin glargine 15 IU/day (glargine) to keep BG levels at a range of 140-180 mg/dl. They found that the average daily glucose level in the glargine group was significantly lower than in the control group, and they concluded that adding insulin glargine to regular protocols successfully lowers BG levels and minimizes the occurrence of hyperglycemia in addition to the need to regular insulin.…”
Section: Discussionsupporting
confidence: 65%
“…In accordance with our results, Nader et al (21) evaluated 110 patients who, besides daily insulin infusions, were randomly assigned to receive adjuvant placebo (control) or insulin glargine 15 IU/day (glargine) to keep BG levels at a range of 140-180 mg/dl. They found that the average daily glucose level in the glargine group was significantly lower than in the control group, and they concluded that adding insulin glargine to regular protocols successfully lowers BG levels and minimizes the occurrence of hyperglycemia in addition to the need to regular insulin.…”
Section: Discussionsupporting
confidence: 65%
“…Intensive glucose control makes it possible to maintain ideal blood glucose levels and avoid extreme variations due to frequent monitoring of blood glucose with prompt intervention in the presence of blood glucose imbalances (Gunst, De Bruyn, & Van den Berghe, 2019). In addition to reducing the development of hyperglycemia, the use of intensive glucose control protocols also aids in decreased infections, hospital complications, all‐cause mortality, and acquired sepsis (Nader et al., 2020; Mahmoodpoor et al., 2016). The use of intensive glucose control protocol has also been associated with an increased risk of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The American Diabetes Association (ADA) recommends a target glucose range of 140–180 mg/dL (7.8–10.0 mmol/L) for the majority of critically ill patients [ 1 ]. It is well documented that hyperglycemia, hypoglycemia, and glucose variability are independent risk factors for mortality of dysglycemic patients in the intensive care unit [ 2 ]. Stress hyperglycemia and diabetes are common conditions in the inpatient setting, with an estimated combined prevalence of 40% and an even higher prevalence in the critically ill.…”
Section: Introductionmentioning
confidence: 99%